Implementation of Human Resources in Efforts Improving the Quality of Work at PT - Hevinanda*, Livia; Kustiningsih, Nanik; Rahayu, Sri (Universitas Syiah Kuala, 2024)
Human Resources (HR) is the company's main milestone in developing and maintaining its existence. Good and quality human resources will also produce high value for the company. In this research, the fact was found that a company can be said to be successful if its support, in this case Human Resources, is also met. Researchers discovered the fact that PT. X as a sample company has experienced downfalls and triumphs due to Human Resources (HR) factors. PT. X is a company that specializes in the field of packaging materials with decades of experience. This company is consistent, professional as a distributor and has a high commitment to providing service to its customers. This company provides services in the field of providing packaging materials such as aluminum foil, polyester and plastic pellets which are commonly used by other companies for produce packaging for their products